CONSERVATION SCIENCE Trends: A Systematic Literature Review of Publications Between 2012-2022 - auliya rohmah, zaenab; Bella Yuyun Ayunda; raviah, azimatur (Journal of Natural Sciences and Learning, 2023)
The purpose of the review article is to find out the research trends related to conservation science, which is very useful for developing teacher learning skills in line with the period of the Industrial Revolution 5.0, which uses a lot of technology integration in learning. In the Industrial Revolution 5.0, technology and humans will coexist to improve human life sustainably. This study is a systematic scientific literature review of the conservation of 500 Google Scholar-indexed journal articles published between 2012 and 2022, but only 17 journal articles that met the requirements were used. The findings show that the regions in Indonesia with the most scientific conservation research are Bandarlampung and North Lampung. Articles related to conservation-scientific research are primarily published in chemistry education and learning journals. Many science education research-based journals have published conservation science articles, but more chemistry coverage still needs to be provided. The most researched topics on the knowledge component in conservation science are colloids, salt hydrolysis, and mixture separation. The least studied are stoichiometry and thermochemistry, meaning these two topics have been of little interest to researchers in the last ten years. From some of the analyses in this literature review, we suggest sharing references and centers for conservation science in science education and formulating what topics need to be researched for further research.